The Asymmetric Arrows of Space-Time in the Evolution of Planet and the Anthropocene (Global Journal of Human-Social Science, 2023)
This article aims to verify the relationship of society with nature, and its thermodynamic energy flows, as an evolutionary element, generating totalization and being analyzed by the arrow(s) of spacetime. This article will also verify how this process influences the formation of the Anthropocene. In this sense, the principles born after the advent of quantum mechanics will be applied to the spatial-temporal analysis of physis (which integrates society-nature). The article also verifies how each formcontent, in a unique way, contributes energetically to the development of its arrow of space-time. Thus, it will also be verified, as, the current production process, is associated, in general, with the disruption of the states of homeotase, in the energetic balance of the process of exchange between energy and matter, and as the old pattern of relative stability, which characterized the Holocene, has been replaced by disorder, which is at the basis of the emergence of the Anthropocene.
Keywords: thermodynamics; anthropocene; holocene; evolution; form-content